A new model of monodeuterated ethane (C2H5D) spectrum: Enabling sensitive constraints on the D/H in ethane emission in comets. (November 2020) - Doney, Kirstin D.; Kofman, Vincent; Villanueva, Geronimo; Sung, Keeyoon
Highlights: High-resolution infrared rovibrational spectrum of C2 H5 D recorded between 2050 - 3050 cm − 1 . Vibrational assignments of eight vibrationally excited states of C2 H5 D is supported by high-level ab initio calculations. Effective spectroscopic parameters of C2 H5 D have been determined from contour fitting. A diagnostic upper limit for D/H in ethane in the comet C/2007 W1 (Boattini) is determined at 18.2 VSMOW. Abstract: Similar to ethane (C2 H6 ), monodeuterated ethane (C2 H5 D) has a bright series of Q-branches in the CH stretch region, between about 2960 - 3020 cm − 1 (3.38 - 3.31 µm). As the progressions in the different isotopes are slightly offset from one another, the new C2 H5 D model enables sensitive constrains of the D/H ratio in spectra from comets, in organics across the Solar System and beyond. Specifically, the D/H ratio of organic molecules in comets is a critical cosmogenic indicator, which not only provides insights into the formation processes of our Solar System, but also allows for a test of our understanding of solid-state astrochemistry. High D/H ratios are predicted in a number of astrochemical models, which can be benchmarked using the new spectroscopic information of C2 H5 D and C2 H6 . We present a quantum band model for C2 H5 D in the mid-infrared. Our model is based on rotationally resolved spectra of C2 H5 D and C2 H6 obtained at 85K between 2050 - 3050 cm − 1 (4.88 - 3.28 µm) using a Bruker IFS-125HR equipped with a cryogenic Herriott cell at JPL. High-level quantum chemical calculations were carried out at the CCSD(T)/ANO1 level of theory to aid vibrational assignments, with the anharmonic frequencies and vibrational corrections determined from second-order vibrational perturbation theory (VPT2). As a first demonstration of the applicability of the model, we obtained a stringent upper limit to the organic D/H ratio (18.2 VSMOW) in comet C/2007 W1 (Boattini) from high resolution fluorescence spectra obtained with Keck/NIRSPEC.